Behaviour of Amorphous Aluminosilicates towards Ageing by High‐Temperature Steaming. Issue 10 (1st September 2014) - Caillot, Maxime; Chaumonnot, Alexandra; Digne, Mathieu; Van Bokhoven, Jeroen A.
Abstract The structure of amorphous aluminosilicates obtained by grafting silicon on alumina (Si/Al2O3) mostly remains the same after ageing by steaming. The rearrangement of surface silicon species on the facets of γ‐alumina slightly decreases the number of Brønsted acid sites, which is determined through ethanol adsorption followed by thermogravimetry as well as m‐xylene isomerisation. Al/SiO2 prepared by grafting aluminium on silica undergoes sintering of the silica support and the agglomeration of the surface aluminium species during steaming. This process leads to a sharp decrease in the number of Brønsted acid sites, which are associated with the dispersed aluminium species, and dehydroxylation of the silica surface.